Improving Students' Reading Skills Utilizing the Kurzweil Program and Practice - Miller, Donna K. (Valdosta State University, 2004)
The purpose of the research was to document the experiences of students as they use the Kurzweil program and practice and to determine if regular use of the program and practice should be recommended as an efficient, effective, and feasible practice in middle school classrooms. The intervention consisted of a series of instructional units taught to three groups of selected students from three intact classes, half of whom were designated with special needs, used the program for a period of four weeks to complete assignments in 7th grade Life Science classrooms. The Kurzweil program provided a synchronized visual and auditory presentation of text. Thirty participants completed all activities. The study included a reading skills pre-test and post-test, teacher observations, student interviews, and a teacher survey. The principal conclusions were that Kurzweil usage was correlated with improved reading scores, students prefer the computer to paper and pencil, and teachers need training. The study indicated the program and practice should be considered as an intervention to assist all students. The results of the study were communicated to the learning community through a PowerPoint presentation at a meeting with teachers and administrators. This meeting supported a recommendation that additional computers and software should be purchased.
Keywords: Kurzweil program; Special needs; Reading skills; Educational technology; Teaching--Aids and devices; Computer-assisted instruction